Pengaruh Current Ratio, Return On Asset dan Ukuran Perusahaan Terhadap Return Saham - Kurnia Dini Asriyanti (JAF (Journal of Accounting and Finance), 2022)
The study aims to analyze the effect of Current Ratio (CR), Return On Asset (ROA) and Firm Size on Stock Return on Food and Beverage Company Listed on Indonesia Stock Exchange for the 2015-2019 period. The data used in this study is secondary data obtained from the financial statements of food and beverage companies listed on the Indonesia Stock Exchange.The population in this study was 63 companies using purposive sampling technique, so that 39 samples of food and beverage sub-sector companies were obtained. The analytical method used in this research is panel data regression with the help of the Eviews 9 program. The results of this study partially show that the variable current ratio, return on assets and firm size have no significant effect on stock returns. While simultaneously the variable current ratio, return on assets and firm size have a significant effect on stock returns.